Differential Expression of Placental Glucocorticoid Receptors and Growth Arrest-Specific Transcript 5 in Term and Preterm Pregnancies: Evidence for Involvement of Maternal Stress - D. Mparmpakas; E. Zachariades; G. Sotiriadis; A. Goumenou; A. J. Harvey; Y. Gidron; E. Karteris (Obstetrics and Gynecology International)
Pregnancy-specific stress predicts birth outcomes. We hypothesized that there is a maternal stress-GR interaction that can influence fetal birth weight. This study examined the relationship between mothers’ stress and attitude towards their pregnancies, placental glucocorticoid receptors (GRs) and growth arrest-specific transcript 5 (GAS5) expression, and the status of GR polymorphism, with their infants’ birth weights. GAS5 and GRα were the predominant transcripts in both term and preterm placentas, with GAS5 being primarily localized in the syncytiotrophoblasts. In an attempt to mimic moderate and high stress environment in vitro, BeWo and JEG-3 cytotrophoblast cell lines were treated with 10 nM–1000 nM cortisol. Only expression of GAS5 was significantly upregulated by cortisol in all treatments compared with basal levels, but none of the GRs changed expression significantly. In an attempt to assess a stress versus gene interaction, we studied four GR polymorphisms. In the homozygous group for Tth111I polymorphism, mothers with negative attitudes towards the pregnancy gave birth to infants with significantly lower birth weights compared to women with positive/neutral attitudes. None of the GR splice variants were associated with maternal stress. However, placental GAS5 levels were inversely correlated with maternal stress. This study points towards a potential gene-environment interaction that could be of predictive value for fetal weight.